Optimizing the Potential of Creativity and Student Learning Outcomes Using the PJBL Learning Model in PKK Subjects at SMK Negeri 6 Surabaya - Putri, Adisty Witama; Mayzura, Elida Cahya; Yohana, Erwanda Febri; Nadiawan, Sonya Putri; Issaura, Yollanda; Dwiyanti, Sri; Panggabean, Sri Lynda Deciana (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study was conducted to analyze the optimization of creativity potential and student learning outcomes in the PKK subject. The method used was Classroom Action Research (CAR) with two cycles, involving 31 students of class XI KC 1 and located at SMKN 6 Surabaya. The results of the study showed a significant increase in the cognitive, psychomotor, and creativity aspects of student learning. The completion of learning the cognitive aspect using the N-Gain test analysis resulted in an increase from 55%. to 71%, with a high category. The learning outcomes of the psychomotor aspect also increased with the analysis using the mean, namely cycle I of 75 to 86 in cycle II. Student creativity increased from cycle I by 68% and cycle II by 86%. Therefore, the optimization of the PJBL model in PKK competencies is said to have succeeded in achieving the completion criteria with a very good category.